Analysis of The Pertalite Queue System For Two-Wheeled Vehicles At ABC Gas Station - Agung Dwi Kurniawan; Anisa Azzahra; Naufal Fathan; Iin Kurnia; Eva Fauziah; Winarno Winarno (Universitas Negeri Padang, 2025)
Abstract – The increasing number of motorcycles in Indonesia has led to growing fuel demand, which in turn results in long queues at gas stations. Although it has eight lanes, long queues, especially for refueling Pertalite on motorcycles, are still an obstacle that has an impact on customer comfort. This study employs a quantitative approach using Promodel software to simulate and analyze queue management at ABC gas stations. Findings indicate that the average customer arrival time is 0.66 minutes, with a service time of 0.58 minutes and an average waiting time of 5.3 minutes. The addition of a dedicated lane for Pertalite refueling significantly reduces queues, improving overall service efficiency and customer satisfaction.